Szigeti on the Violin - Szigeti, Joseph 1892-1973; Hughes, Spike 1908-1987 (New York Dover, 1979)
In 'Szigeti on the Violin', Szigeti presents his opinions about the then-current state of violin playing and the various challenges and issues facing musicians in the modern world, as well as a detailed examination of violin technique as he understood it.A recurring theme in the first part is the changing nature of violinist's lives during Szigeti's later years. In his youth, concert artists relied primarily on recitals to establish themselves and attract critical attention and acclaim; by the time of Szigeti's writings, the recital had been eclipsed in importance by the competition. Szigeti was dismayed by this trend, especially since he considered the fast-paced and intense preparation necessary for high-level competitions to be "…incompatible with the slow maturing either of the performing artist or of the repertoire." Szigeti believed that such accelerated development of a musician led to performances that "lack(ed) the stamp of authenticity, the mark of a personal view evolved through trial and error." In a similar vein, he was skeptical of the effects produced by the recording industry on the culture of music-making. In Szigeti's opinion, the allure of the recording contract and the instant "success" that it implied led many young artists to record works before they were musically ready, and thus contributed to the problem of artificially fast development and resulting musical immaturity.Szigeti also offers a lengthy and detailed explanation of his approach to violin technique. He believed that a violinist should be concerned primarily with musical goals, rather than simply choosing either the easiest or most impressively virtuosic way to play a certain passage. He was particularly concerned with tone color: he advised that "The player should cultivate a seismograph-like sensitivity to brusque changes of tone colour caused by fingerings based on expediency and comfort rather than the composer’s manifest or probable intentions." Other topics prominently discussed include the most effective position of a violinist's left hand, the violin works of Béla Bartók, a cautionary list of widely accepted misprints and editorial inaccuracies in the standard repertoire, and most notably, the vital importance of J.S. Bach's Six Sonatas and Partitas for any violinist's technical and artistic development.
Includes index.
Keywords: 20th Century (1901-2000); Violinist; Violin; Musical interpretation; Bowing; Orchestra; Music philosophy and esthetics; Biography